Overview of the Use of Murine Models in Leukemia and Lymphoma Research - Kohnken, Rebecca; Porcu, Pierluigi; Mishra, Anjali (Frontiers in Oncology, 2017)
Murine models have been adopted as a significant and powerful tool in the study of cancer. The applications of murine models of cancer are numerous: mechanism discovery, oncogenesis, molecular genetics, microenvironment, metastasis, and therapeutic efficacy. Leukemias and lymphomas are a group of highly heterogeneous hematologic malignancies that affect people of all ages and ethnicities. Leukemia and lymphoma arise from hematopoietic and immune cells and usually spread widely throughout the body. The liquid nature of many of these malignancies, as well as the complex microenvironment from which they arise and their multifaceted genetic basis, has added to the difficulty in generating appropriate and translational models to study them. Murine models of leukemia and lymphoma have made substantial contributions to our understanding of the pathobiology of these disorders in humans. However, while there are many advantages to these models, limitations remain. In this review, we discuss the mouse as a model to study leukemia and lymphoma, and the importance of choosing the correct methodology. Specific examples of murine models of leukemias and lymphomas are provided, with particular attention to those that are highly translational to their human counterpart. Finally, future applications of murine models and potential for better models are discussed.